ATIM-04. PHASE I IMMUNOVIROTHERAPY TRIAL OF IL-12 EXPRESSING HSV-1 (M032) IN PET DOGS WITH SPONTANEOUS HIGH GRADE GLIOMAS: A PRELIMINARY REPORT. (11th November 2019) - Renee Chambers, M; Crossman, David; Foote, Jeremy; Koehler, Jey; Markert, James; Platt, Simon; Mitchell Self, D; Shores, Andy; Waters, Alicia; Yanke, Amy; Yancey Gillespie, G
Abstract: Malignant gliomas are the most common primary brain tumors in humans, accounting for approximately 30% of all primary central nervous system (CNS) tumors in adults. Incidence and outcomes of gliomas in pet dogs are similar to humans. Previous methods of studying gliomas in rodent models do not adequately represent several features that define human cancers, most notably the sporadic nature of tumor development. Murine models lack intra-tumoral heterogeneity or hosts do not have an intact immune system. To overcome these rodent model deficiencies, many investigators have used canine models to study human diseases. We describe a prospective, phase I clinical trial in canine patients with sporadic high-grade gliomas to evaluate M032, a mutant HSV-1 expressing IL-12, alone or combined with a checkpoint inhibitor (Indoximod) to assess safety, tolerability and efficacy. M032 has been shown to infect and kill glioma cells, producing a virus and tumor cell antigen-rich debris field; will provide an increased adjuvant effect from released viral DNA recognized by TLR-9 receptors; and express IL-12 locally, stimulating activation of TH 1 lymphocytes. The intratumoral inflammatory cell infiltration is expected to result in immune-related anti-viral responses with cross-epitope spreading to tumor antigens. Indoximod immunomodulation will be tested in latter cohorts to prolong anti-tumor responses. To date, six canines with high-grade gliomas have received intratumoral M032 without virus-related toxicities. Resected tumor and serial blood samples are being cryopreserved for analysis of lymphoid and monocyte/myeloid subset markers. This same virus is being tested in a phase 1 clinical trial in humans with high-grade malignant gliomas; eight human patients have received treatment at this writing without virus-related toxicities. The concurrent prosecution of both trials allows unprecedented real time comparison of safety and efficacy of immunovirotherapy as a stringent test of suitability of the dog as a valid and informative model of human brain tumors.